Students’ Perceptions Towards Teaching Speaking - Mutaat Mutaat (Acitya: Journal of Teaching and Education, 2022)
The present study aimed to identify the students’ perceptions on their speaking practices conducted by their teachers during the class. The present study was a survey research involving 40 students of a privately funded language college. As a survey research, the present study focused on the student’s responses given during the administration of the questionnaire as the only instrument given to them. The students’ perceptions indicated from their written responses were further calculated in order to find the most frequent or the most dominant answers. The findings indicated that the students preferred to have more interesting topic that was used to discuss or interact among their friends during the oral practice. They also thought that the use of simple handouts could be useful as these did not burden the students when practicing their language. Lastly, they also thought that, despite having a good or interesting topic, they still needed the teacher to facilitate their speaking practice.